2007
DOI: 10.1088/0960-1317/17/8/031
|View full text |Cite
|
Sign up to set email alerts
|

A low actuation voltage electrostatic actuator for RF MEMS switch applications

Abstract: This paper presents the design, fabrication and characterization of an RF MEMS switch. Low actuation voltage and high isolation of the switch were achieved by exploiting buckling and bending effects induced by well-controlled residual stress. The effects of residual stress on improving the switch performance have been investigated using both analytical and numerical methods. The proposed RF switch has been fabricated by surface micromachining. The minimum actuation voltage of the fabricated switch was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(39 citation statements)
references
References 25 publications
0
38
0
1
Order By: Relevance
“…This is one of the reasons why work is underway with the aim of reducing the actuation voltage requirements for new devices [21,[44][45][46][47] and designing optimised actuation waveforms [59][60][61][62] for minimal dielectric charging.…”
Section: High Voltages or Currentsmentioning
confidence: 99%
“…This is one of the reasons why work is underway with the aim of reducing the actuation voltage requirements for new devices [21,[44][45][46][47] and designing optimised actuation waveforms [59][60][61][62] for minimal dielectric charging.…”
Section: High Voltages or Currentsmentioning
confidence: 99%
“…Balaraman et al [7] fabricated a low cost and actuation voltage RF micro switch using copper. Taking advantage of residual stress to induce buckling and bending, Chu et al [8] designed a high-isolation and low actuation voltage RF micro switch. Khater et al [9] demonstrated 60 % voltage reduction by changing the actuation mode from static to dynamic pull-in.…”
Section: Introductionmentioning
confidence: 99%
“…The S shape has also been used for a novel micromechanical optical switch [19] and a microvalve [20,21]. Some RF switches have beam structures that offer the same advantage [22]. The S shape makes the gap between electrodes small at the edge, and the electrostatic force works effectively at the edge.…”
Section: Introductionmentioning
confidence: 99%